Optimal body size adjustment of L3 CT skeletal muscle area for sarcopenia assessment - Brian A. Derstine (Nature Portfolio, 2021)
Abstract Measurements of skeletal muscle cross-sectional area (SMA) at the level of the third lumbar (L3) vertebra derived from clinical computed tomography (CT) scans are commonly used in assessments of sarcopenia, the loss of skeletal muscle mass and function associated with aging. As SMA is correlated with height and Body Mass Index (BMI), body size adjustment is necessary to fairly assess sarcopenic low muscle mass in individuals of different height and BMI. The skeletal muscle index, a widely used measure, adjusts for height as $$(SMA/height^2)$$ ( S M A / h e i g h t 2 ) but uses no BMI adjustment. There is no agreed upon standard for body size adjustment. We extracted L3 SMA using non-contrast-enhanced CT scans from healthy adults, split into ‘Under-40’ and ‘Over-40’ cohorts. Sex-specific allometric analysis showed that height to the power of one was the optimal integer coefficient for height adjusted SMA in both males and females. We computed two height-adjusted measures $$SMA_{HT}=SMA/height$$ S M A HT = S M A / h e i g h t and $$SMA_{HT2}=SMA/height^2$$ S M A H T 2 = S M A / h e i g h t 2 , comparing their Pearson correlations versus age, height, weight, and BMI separately by sex and cohort. Finally, in the ‘Under-40’ cohort, we used linear regression to convert each height-adjusted measure into a z-score ( $$z(SMA_{HT})$$ z ( S M A HT ) , $$z(SMA_{HT2})$$ z ( S M A H T 2 ) ) adjusted for BMI. $$SMA_{HT}$$ S M A HT was less correlated with height in both males and females ( $$r=0.005$$ r = 0.005 , $$p=0.91$$ p = 0.91 and $$r=0.1$$ r = 0.1 , $$p=0.01$$ p = 0.01 ) than $$SMA_{HT2}$$ S M A H T 2 ( $$r=-\,0.30$$ r = - 0.30 and $$r=-\,0.21$$ r = - 0.21 , $$p<0.001$$ p < 0.001 ). $$z(SMA_{HT})$$ z ( S M A HT ) was uncorrelated with BMI and weight, and minimally correlated with height in males and females ( $$r=-\,0.01$$ r = - 0.01 , $$p=0.85$$ p = 0.85 and $$r=0.15$$ r = 0.15 , $$p<0.001$$ p < 0.001 ). The final $$z(SMA_{HT})$$ z ( S M A HT ) equation was: $$z = (I - {\widehat{I}}) / SD(I)$$ z = ( I - I ^ ) / S D ( I ) , where $$I = SMA/height$$ I = S M A / h e i g h t , $${\widehat{I}} = 50 + BMI + 13 × sex + 0.6 × BMI × sex$$ I ^ = 50 + B M I + 13 × s e x + 0.6 × B M I × s e x , $$SD(I) = 8.8 + 2.6 × sex$$ S D ( I ) = 8.8 + 2.6 × s e x , and sex = 1 if male, 0 if female. We propose $$SMA_{HT}$$ S M A HT for optimal height adjustment and the $$z(SMA_{HT})$$ z ( S M A HT ) score for optimal height and BMI adjustment. By minimizing correlations with height and BMI, the $$z(SMA_{HT})$$ z ( S M A HT ) score produces unbiased assessments of relative L3 skeletal muscle area across the full range of body sizes.